ANALISIS KINERJA PROFITABILITAS PT. BANK NEGARA INDONESIA (PERSERO) Tbk PERIODE 2017-2021 - Nabila Nur Sadrina (2023)
Bank Negara Indonesia is one of the state-owned commercial bank whose business scope is international, as evidenced by 9 overseas office networks. Public trust in a bank is influenced by the company's ability to generate profits (profits) from sales, assets and return on equity (earnings), as measured by the bank own profitability ratio. The purpose of the research conducted is to determine the level of profitability of Bank BNI for the period 2017-2021 using the profitability ratios ROA, ROE and NPM. the results of this study indicate that the level of ROA, ROE and NPM Bank BNI "fluctuating" based on data processed by the author from the financial statements and profit and loss statements of BNI bank for the period 2017-2021. Keywords: Profitability, ROA, ROE, NPM